Implementation of Management Function to Corn fritter Enterpreneurs in Padang Panjang City - Sofiani, Hernifa; Yulastri, Asmar; Gusnita, Wiwik; Indrayeni, Wiwik (Universitas Negeri Padang, 2024)
This research is based on the background of corn business actors who are still facing challenges in applying management principles so that the production produced is not effective and efficient. The purpose of the study is to describe production management in corn farming business actors in Padang Panjang City. The type of research used is qualitative, carried out in Padang Panjang City in July 2024. The source of research data was obtained from informants, namely corn business actors. Data collection techniques by conducting observations, interviews, and documentation. The data analysis used includes data reduction, data presentation, and conclusion drawn. The results of the study show that corn farmers in Padang Panjang City are quite good in carrying out management functions, namely: planning, organizing, directing and supervising the corn production process.